THE ROLE OF THE FAMILY PHYSICIAN IN THE EARLY DETECTION OF DIABETES MELLITUS - Abobakirova Odinaxon Olimjon qizi (TADQIQOTLAR, 2025)
ANNOTATION This annotation examines the critical role of family physicians in the early detection and management of diabetes mellitus. Diabetes, particularly type 2, has become a major global health concern due to its increasing prevalence, long-term complications, and substantial economic burden. Early identification of diabetes is essential to prevent or delay complications such as cardiovascular disease, nephropathy, neuropathy, and retinopathy. Family physicians, as primary healthcare providers, are ideally positioned to implement screening programs, identify at-risk individuals, and provide timely interventions.